Development of Interactive Learning Multimedia Based on Guided Inquiry to Improve Student Learning Outcomes in Science Content Material Force, Motion and Energy Transfer Class VI SDN Bumi Arum - Hendra, Zul; Kurniati, Nia (FONDATIA, 2024)
Class VI science material includes concepts that are fundamental and essential for scientific understanding. However, conventional learning approaches often do not fully utilize students' potential to actively participate in the learning process. Therefore, the development of interactive learning multimedia based on Guided Inquiry is expected to provide a more interesting and effective alternative in teaching these concepts. This study aims to develop and test the effectiveness of Guided Inquiry-Based Interactive Learning Multimedia in increasing students' understanding of Force, Motion, and Energy Transfer material in grade VI science lessons. The method used in writing this journal is based on qualitative writing using a descriptive approach of analysis. The writing technique is based on qualitative data. The results of the field test revealed that the average value obtained increased to 78.79 which was previously 69.68. In addition, based on the results of the study also explained that the use of guided inquiry implemented in science learning media, especially in style material gets better results compared to the use of conventional learning, namely by using textbooks during learning activities. This is proven through a hypothesis test that the value of t table is 2.001 while t count is 2.76. By using guided inquiry models on the topics of interactive multimedia-assisted learning of force, motion, and energy transfer, student learning outcomes can be improved.